Elevated temperature drives a shift from selfing to outcrossing in the insect-pollinated legume, faba bean (Vicia faba) - Bishop, Jacob (Journal of experimental botany, 2017)
© The Author 2016. Published by Oxford University Press on behalf of the Society for Experimental Biology.